A Design and Build Information Systems Project Management Web-Based Student Attendance at Rancaekek Bintara Vocational School - Budiman, Tedi; Rosliani, Elin; Muhamad Ramdan, Dandi (RISTEC : Research in Information Systems and Technology, 2023)
The web-based student attendance information system at SMK Bintara Rancaekek is designed and built to enhance the efficiency and accuracy of attendance recording. The methodology used in this study is Linear Sequential, which includes the stages of analysis, design, coding, and testing. This attendance information system is developed using the PHP programming language and MySQL database. To support system design, UML (Unified Modeling Language) diagrams are used, including use case, activity, class, and sequence diagrams. The result of this study is a system that allows teachers and administrative staff to record student attendance in real-time, access attendance reports, and manage student data more easily. Trials show that this system improves operational efficiency and reduces attendance recording errors. This web-based attendance information system is expected to support school administration management and provide significant benefits to SMK Bintara Rancaekek